2017
DOI: 10.1038/s41598-017-04232-4
|View full text |Cite
|
Sign up to set email alerts
|

Synuclein impairs trafficking and signaling of BDNF in a mouse model of Parkinson’s disease

Abstract: Recent studies have demonstrated that hyperphosphorylation of tau protein plays a role in neuronal toxicities of α-synuclein (ASYN) in neurodegenerative disease such as familial Alzheimer’s disease (AD), dementia with Lewy bodies (DLB) and Parkinson’s disease. Using a transgenic mouse model of Parkinson’s disease (PD) that expresses GFP-ASYN driven by the PDGF-β promoter, we investigated how accumulation of ASYN impacted axonal function. We found that retrograde axonal trafficking of brain-derived neurotrophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 65 publications
3
78
0
Order By: Relevance
“…Thus, elevated expression of Rab5b and Rab7 may indicate the internalized molecules undergo a quick Rab5 to Rab7 conversion before taking any effects. In line with our results, a recent study observed enhanced expression of Rab5 in PD mouse model overexpressing wild-type α -syn 27 .…”
Section: Resultssupporting
confidence: 93%
“…Thus, elevated expression of Rab5b and Rab7 may indicate the internalized molecules undergo a quick Rab5 to Rab7 conversion before taking any effects. In line with our results, a recent study observed enhanced expression of Rab5 in PD mouse model overexpressing wild-type α -syn 27 .…”
Section: Resultssupporting
confidence: 93%
“…At DIV9, we then used a well-established system to measure retrograde axonal transport of quantum dot-labeled BDNF (QD-BDNF) by live cell imaging (8, 20, 3335). Interestingly, CCT5-lenti treatment enhanced retrograde axonal transport of BDNF in comparison to control lenti as revealed by kymograph analysis (Figure 1C-H); it resulted in an increase in instantaneous velocity (the absolute velocity from moving time without pause time included) from 1.33 ± 0.08 μm/s to 1.62 ± 0.08 μm/s (Figure 1C, D) and a decrease in the percentage of pause events (from 19 ± 3% to 12 ± 2%) (Figure 1C, E) and average pause duration (from 7.47 ± 1.17 s to 4.16 ± 0.74 s) (Figure 1C, F).…”
Section: Resultsmentioning
confidence: 99%
“…At DIV9, we used a well-established system to measure retrograde axonal transport of quantum dotlabeled BDNF (QD-BDNF) by live cell imaging. 8,20,[33][34][35] Interestingly, We next investigated whether CCT5-induced enhancement of axonal transport function was tau-dependent, as tau plays an important role in modulating axonal transport under both physiological and pathological conditions. 22 To establish a role of tau in CCT5-mediated enhancement of axonal transport of BDNF, we elect to examine E18 cortical neurons from tau −/− mouse ( Figure 2).…”
Section: Cct Modulates Axonal Transport Of Bdnf Via a Tau-dependentmentioning
confidence: 99%
“…This establishes an additional perspective -cell-autonomous neuronal pathophysiology -in the etiology of PD to complement well-established pathological and molecular approaches. It also provides a novel set of questions for follow-up studies to understand which molecular and cell-biological mechanisms induce a-synuclein-mediated shrinkage and channel dysregulation (Fang et al, 2017;Ulusoy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our data argue against an upregulation of functional Kv4 channels, because the total whole-cell Kv4 current did not differ between the AAV treatments (data not shown), pointing to an alternative mechanism. An a-synuclein-induced, cell-autonomous shrinkage of vagal motoneurons causes a selective dysregulation of Kv4 current densities a-Synuclein overexpression has been shown to cause vagal motoneurons (Ulusoy et al, 2015) and other neuronal types (Fang et al, 2017) to shrink. Indeed, measurement of the long axis of the somata of DMV neurons from animals transfected with AAV-A53T demonstrated that it was shorter in human a-synuclein-positive DMV neurons in comparison to neighboring human a-synuclein-negative DMV neurons ( Fig.…”
Section: Figure 2 Gastrointestinal Motility Is Slowed In the Mouse Mmentioning
confidence: 99%